2020
DOI: 10.1101/2020.05.10.079236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding partners regulate unfolding of myosin VI to activate the molecular motor

Abstract: Myosin VI is the only minus-end actin motor and is coupled to various cellular processes ranging from endocytosis to transcription. This multipotent nature is achieved through alternative isoform splicing and interactions with a network of binding partners. How the regulation mechanism of myosin VI varies between different isoforms and binding partners remains unexplored. Here, we have compared the regulation of two myosin VI splice isoforms by two different binding partners. By combining biochemical and singl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To further address this point, we performed single molecule localisation microscopy (STORM) analysis with the 50A guide 2 h measurement ( Figure 4 G). This approach is equivalent to the widefield imaging performed in Figure 2 and Figure 3 , but with approximately five-fold increased resolution and the ability to count single molecules and quantify clusters [ 21 , 22 ]. We detected γH2AX foci and then quantified the foci using cluster analysis ( Figure 4 H).…”
Section: Resultsmentioning
confidence: 99%
“…To further address this point, we performed single molecule localisation microscopy (STORM) analysis with the 50A guide 2 h measurement ( Figure 4 G). This approach is equivalent to the widefield imaging performed in Figure 2 and Figure 3 , but with approximately five-fold increased resolution and the ability to count single molecules and quantify clusters [ 21 , 22 ]. We detected γH2AX foci and then quantified the foci using cluster analysis ( Figure 4 H).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that full-length NDP52 is mainly a dimer in solution 6,9 . To confirm this, we used Size-Exclusion Chromatography with Multi-Angle Light Scattering (SEC-MALS).…”
Section: Ndp52 Oligomerisation and Structurementioning
confidence: 98%
“…At the C-terminal, ZF1 has been characterised as an unconventional dynamic zinc finger, whilst ZF2 is a canonical C2H2-type zinc finger 7 . The C-terminal domains of NDP52 are responsible for interactions with ubiquitin, which allows binding to ubiquitylated pathogens, as well as interactions with actin-based motor Myosin VI (MVI) 3,[7][8][9] . In the cytoplasm, interactions between NDP52 and MVI allow autophagosome maturation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To further address this point, we performed single molecule localisation microscopy (STORM) analysis with the 50A guide 2-hour measurement ( Figure 4G). This approach is equivalent to the widefield imaging performed in Figure 2 and 3, but with approximately five-fold increased resolution and the ability to count single molecules and quantify clusters 18,19 . We detected gH2AX foci and then quantified the foci using cluster analysis ( Figure 4H).…”
Section: Tuning the Number Of Dna Damage Sites Using Cas9 And Promiscmentioning
confidence: 99%